Impact of a dental care program on the quality of life of children with and without caries - Janice Simpson de PAULA; Karin Luciana Migliato SARRACINI; Gláucia Maria Bovi AMBROSANO; Antônio Carlos PEREIRA; Marcelo de Castro MENEGHIM; Fábio Luiz MIALHE
Abstract: The aim of the present study was to evaluate the long-term effects of the caries treatment provided by a dental care program on changes in schoolchildren's OHRQoL. A one-year follow-up was conducted with a sample of 372 children aged 8 to 10 years which were clinically examined and divided into two matched groups according to their caries experience: dental treatment group (DTG) and group without caries (GWC). Both groups were assessed three times (at baseline, at 4 weeks, and at 1 year) using the Child Perceptions Questionnaire (CPQ8-10). The normality test was performed for the statistical analyses; the Friedman test was used for the dependent variables (longitudinal assessment repeated three times for the same group); and the Mann-Whitney test was used for the independent variables (test and control groups in each time period). There was improvement in all domains and in overall CPQ8-10 (p < 0.0001) in the DTG over time, but no significant changes (p > 0.05) were observed at baseline for overall CPQ8-10 and for the emotional well-being domain in the GWC. The comparison between groups demonstrated that OHRQoL was persistently better for the GWC (p < 0.05) over time. In conclusion, dental caries treatment has a long-term positive impact on schoolchildren's OHRQoL, highlighting the importance of health policies that promote access to dental care for this population.